Seroreversion of IgG anti‐HEV in HIV cirrhotic patients: A long‐term multi‐sampling longitudinal study. Issue 5 (3rd March 2022) - López‐López, Pedro; Frias, Mario; Camacho, Angela; Machuca, Isabel; Caballero‐Gómez, Javier; Risalde, María A.; García‐Bocanegra, Ignacio; Pérez‐Valero, Ignacio; Gomez‐Villamandos, Jose C.; Rivero‐Juárez, Antonio; Rivero, Antonio
Abstract: The aim of our study was to evaluate HEV antibody kinetics in HIV/HCV‐coinfected patients with cirrhosis. A longitudinal retrospective study was designed. Patients were followed up every 6 months; anti‐HEV IgG and IgM antibodies levels and HEV‐RNA by qPCR were analysed. The prevalence and incidence of every HEV infection marker were calculated. The kinetics of anti‐HEV IgG and IgM during the follow‐up were evaluated. Seventy‐five patients comprised the study population. The seroprevalence observed was 17.3%. None showed IgM antibodies or HEV‐RNA at baseline. None showed detectable HEV viral load during the study period. After a median follow‐up of 5.1 years, two of 62 seronegative patients (3.2%) seroconverted to IgG antibody. The incidence for IgM was 2.7%. Of the 13 patients with IgG seropositivity at baseline, five (38.5%) seroreverted. Meanwhile, of the two patients who exhibited IgM positivity during the study, one (50%) showed intermittent positivity. We found that HEV seropositivity is common in HIV/HCV‐coinfected cirrhotic patients. A remarkable rate of IgG seroreversions and IgM intermittence was found, limiting the use of antibodies for the diagnosis of HEV infection in this population.